Wedelolactone-Loaded Micelles Ameliorate Doxorubicin-Induced Oxidative Injury in Podocytes by Improving Permeability and Bioavailability - Feng, Liang; Li, Zhi-yong; Wang, Long; Li, Xing-hua; Chen, Ya-ping; Yang, Bing; Yang, Dang; Lian, Yuan-pei; Hou, Xue-feng; Li, Jun-hui; Ding, Shu-min; Jia, Xiao-bin (Frontiers in Bioengineering and Biotechnology, 2019)
Wedelolactone (WED) is commonly used for the treatment of doxorubicin (DOX) - induced kidney damage, but its efficacy is limited by its poor solubility and bioavailability. In this study, we developed a novel delivery system of WED-loaded micelles (WED-M) with Solutol® HS15 and lecithin at an optimized ratio of 7:3 to improve the poor permeability and bioavailability of WED and to enhance its efficacy. The spherical-shaped WED-M (particle size : 160.5±3.4 nm; zeta potential : -30.1±0.9 mV; entrapment efficiency: 94.41±1.64%; drug loading: 8.58±0.25%; solubility: 1.89±0.06 mg/ml) has a continuous stability within 14 days and a sustained release profile. The permeability of WED-M in Caco-2 cells indicated a significant 1.61-fold higher of Papp AP to BL than WED only. Additionally, pharmacokinetics evaluation of WED-M demonstrated the bioavailability of WED was increased by 2.78-fold. Both HE staining and transmission electron microscope observed an obvious improvement on pathological damage in WED-M treatment. Moreover, WED-M significantly enhanced ROS level in mice and podocytes MPC5 cells. We concluded that the micelles delivery system WED could improve its permeability and bioavailability to attenuate DOX- induced oxidative injury in podocytes. This study provided important information on a fact that micelles delivery system WED-M showed a significant improvement on renal damage.